Eating disorders risk assessment and body esteem among elite polish contact karate athletes - Dobkowska-Szefer, Daria; Staśkiewicz-Bartecka, Wiktoria; Kiciak, Agata; Kardas, Marek (Frontiers in Nutrition, 2025)
BackgroundThe prevalence of disordered eating behaviors and body image disturbances among athletes in weight-category sports remains insufficiently explored, especially in combat disciplines such as contact karate. The present study aimed to assess the risk of eating disorders and body image perception among elite Polish contact karate athletes, considering the influence of competitive pressure, weight-category requirements, and body image ideals on nutritional behaviors and mental health.MethodsThis cross-sectional descriptive study involved 55 elite contact karate athletes, all with at least one medal at the Polish Championships or higher level competitions. Data were collected using a computer-assisted web interview (CAWI) and validated tools: the Eating Attitudes Test (EAT-26), the Düsseldorf Orthorexia Scale (DOS-PL), and the Body Esteem Scale (BES).ResultsApplying all three EAT-26 referral criteria, 58.12% of athletes threshold indicating potential eating-disorder risk; 12.73% screened positive on the EAT-26 symptom score (Part A), which evaluates attitudes toward eating and dieting behaviors, reflecting one’s relationship with food. On DOS-PL, 10.9% met the orthorexia cut-off and a further 20% were at elevated risk. Weight-making behaviors were common 47.47% reported cutting weight, typically ~4.6% body mass per event. Sex differences emerged: women scored higher on EAT-26 Part A (p = 0.021) and reported lower body-esteem in sexual attractiveness and weight control, whereas men most often reported medium physical attractiveness with frequent low ratings for upper-body strength/physical condition. In women, higher body-esteem correlated with lower EAT-26 totals, and EAT-26 correlated positively with DOS-PL (r = 0.367, p = 0.036); these associations were not observed in men.ConclusionThe finding that over half of elite contact karate athletes exhibit risk indicators for eating disorders highlights the urgent need for systematic screening and intervention in weight-category sports. Prevention programs should integrate nutritional education, mental health support, and early identification strategies to protect both performance and long term health.